Sparing Land for Biodiversity at Multiple Spatial Scales - Ekroos, Johan; Ödman, Anja M.; Andersson, Georg K. S.; Birkhofer, Klaus; Herbertsson, Lina; Klatt, Björn K.; Olsson, Ola; Olsson, Pål Axel; Persson, Anna S.; Prentice, Honor C.; Rundlöf, Maj; Smith, Henrik G. (Frontiers in Ecology and Evolution, 2016)
A common approach to the conservation of farmland biodiversity and the promotion of multifunctional landscapes, particularly in landscapes containing only small remnants of non-crop habitats, has been to maintain landscape heterogeneity and reduce land-use intensity. In contrast, it has recently been shown that devoting specific areas of non-crop habitats to conservation, segregated from high-yielding farmland (‘land sparing’), can more effectively conserve biodiversity than promoting low-yielding, less intensively managed farmland occupying larger areas (‘land sharing’). In the present paper we suggest that the debate over the relative merits of land sparing or land sharing is partly blurred by the differing spatial scales at which it is suggested that land sparing should be applied. We argue that there is no single correct spatial scale for segregating biodiversity protection and commodity production in multifunctional landscapes. Instead we propose an alternative conceptual construct, which we call ‘multiple-scale land sparing’, targeting biodiversity and ecosystem services in transformed landscapes. We discuss how multiple-scale land sparing may overcome the apparent dichotomy between land sharing and land sparing and help to find acceptable compromises that conserve biodiversity and landscape multifunctionality.